Seagrass Connectivity Based on Oceanographic Condition in The Marine Protected Area of Biawak Islands, Indramayu - Aditya Ramadhan; Noir Primadona Purba; Sunarto Sunarto; Udhi Eko Hernawan; Ibnu Faizal (Jurnal Segara, 2022)
Seagrasses are an essential component of the coastal environment with provide many ecosystem services beneficial to humans. Understanding the pattern of dispersal of segrasses is important for conservation management. The aimed of this research was to analyze the seed dispersal of the seagrass Enhalus acoroides in the Marine Protected Area of Biawak Islands, Indramayu, based on hydrodynamic modelling. Oceanographic data were downloaded from several open acces website and location of seagrasses based one insitu observation. Then, oceanographic parameters and seed traits were used to develop the particle trajectory model. Our analysis showed that the seafloor’s depth around the islands varied, ranging from 8 m to 48 m. The seed dispersal was strongly influenced by alternating tidal currents (reversing current). The particle trajectory showed that most of the seeds would be transported outward away from each source in the islands, and they settled in deeper areas further from the coast of the islands. This result indicates that the seagrass population in Biawak Islands might depend predominantly on vegetative recruitment, which is slow. This may be related to the low seagrass canopy cover in Biawak Islands.